PENERAPAN STRATEGI CARD SHORT DALAM PEMBELAJARAN TARKIB PADA SISWI SMAI SUNAN GUNUNG JATI - Mardiyah, Hanik Shofa; Ana Durrotul Hikmah (STAI KH. Muhammad Ali Shodiq, 2024)
Card short is one of the learning strategies that teachers can use to facilitate Tarkib learning so that students have the ability to understand Arabic learning texts easily. In the Short Card Strategy, a student can measure the extent of the understanding he gets from a Tarkib learning process. This study aims to describe the application of the short card strategy in learning tarkib in SMAI Sunan Gunung Jati students in the Sunan Pandanaran Ngunut girls' dormitory, especially in increasing students' activeness in learning Arabic. The method used in this study is qualitative descriptive with the type of field research. The results of the study show that the short card strategy in learning tarkib used by Arabic teachers at SMAI Sunan Gunung Jati can identify the extent of students' understanding in the learning process and also increase students' interest and activeness in learning Arabic.